(untitled) (Research, Society and Development, 2024)
Diabetes mellitus is a chronic endocrine condition manifested by persistent hyperglycemia due to a deficiency in insulin production or action. This study aims to examine how prolonged use of glucocorticoids can cause diabetes mellitus in cats. The methodology consisted of a comprehensive literature review using scientific databases such as PubMed, Scopus and Web of Science. A review of relevant articles was carried out, which included original studies and reviews published in peer-reviewed journals. These articles examined the association between glucocorticoids and diabetes mellitus in cats. Inclusion requirements included full texts in English, Spanish or Portuguese. The results show that prolonged use of glucocorticoids can cause insulin resistance and hyperglycemia, increasing the risk of secondary diabetes mellitus in cats. Conditions such as hyperlipemia and redistribution of body fat are caused by changes in glucose metabolism as a result of prolonged administration of these drugs. Insulin resistance caused by glucocorticoids makes normal glucose regulation more difficult, which leads to the development of diabetes mellitus. In view of this, it is stated that prolonged use of glucocorticoids can cause diabetes mellitus in cats by negatively affecting insulin sensitivity and glucose metabolism. The review indicates that the administration of glucocorticoids should be closely monitored and adjusted to reduce the risk of diabetes mellitus and other associated complications in cats.